Candida albicans skin infection in patients with type 2 diabetes: a systematic review and meta-analysis - Rasoulpoor, Shna; Shohaimi, Shamarina; Salari, Nader; Raygani, Aliakbar Vaisi; Rasoulpoor, Shabnam; Shabani, Shervin; Jalali, Rostam; Mohammadi, Masoud (Elsevier, 2021)
Background: Fungal infections including Candida albicans is one of the most important health concerns among type 2 diabetic patients. Therefore, this study aimed to determine the prevalence of C. albicans skin infection in patients with type 2 diabetes in a systematic review and meta-analysis. Methods: In this review study, data were extracted from national and international databases of SID, MagIran, IranMedex, IranDoc, Google Scholar, Cochrane, Embase, ScienceDirect, Scopus, PubMed, and Web of Science (WoS) with no time limit until January 2021. The random effects model was used for doing analysis and the I2 index was used for assessing the heterogeneity of studies. Data were analyzed using Comprehensive Meta-Analysis (Version 2). Results: The prevalence of C. albicans skin infection in patients with type 2 diabetes was 11.4% (95% CI: 8.9%-14.4%) in 13 reviewed articles with a sample size of 1348. Regarding the heterogeneity based on meta-regression, there was a significant difference between the effect of sample size (P < 0.05) and the prevalence of C. albicans skin infection in patients with type 2 diabetes. Conclusion: The results of this study showed that C. albicans skin infection was high in type 2 diabetic patients in Iran. Therefore, to improve the aforementioned situation and to troubleshoot and monitor at all levels, appropriate policies should be adopted.